2009
DOI: 10.1111/j.1472-8206.2009.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of therapeutic drug monitoring of protease inhibitors in HIV‐infected patients depends on PI used in HAART regimen – ANRS 111 trial

Abstract: As a result of high inter-patient variability, and efficacy-concentration and toxicity-concentration relationships, optimization of HIV-protease inhibitor (PI) doses based on plasma concentrations could be beneficial. During a 48-week open prospective non-randomized interventional study of 115 protease inhibitor-naïve patients initiating an indinavir/ritonavir- or lopinavir/ritonavir-, or nelfinavir-containing therapy, protease inhibitor dose was modified when plasma trough concentrations (C(trough)) at weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Using likelihood ratio test to compare the efficacy of the three studied PI, we found a significant difference in the efficacy of nelfinavir compared to lopinavir or indinavir. This is in agreement with the results of the trial (Duval et al, 2009) in which virological failure was found in 33% of patients treated with nelfinavir and only in 5% of patients treated by indinavir or lopinavir.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using likelihood ratio test to compare the efficacy of the three studied PI, we found a significant difference in the efficacy of nelfinavir compared to lopinavir or indinavir. This is in agreement with the results of the trial (Duval et al, 2009) in which virological failure was found in 33% of patients treated with nelfinavir and only in 5% of patients treated by indinavir or lopinavir.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma HIV-1-RNA were measured by Roche monitored with a LOQ of 50 copies/ml. The results of this trial are reported in Duval et al (2009). The proportion of virological failure was higher in the nelfinavir group and similar for indinavir and lopinavir, although lopinavir is supposed to be a more potent PI now widely used.…”
Section: Application To the Cophar2-anrs111 Trial 41 Materials And Mementioning
confidence: 88%
See 1 more Smart Citation
“…The COPHAR2-ANRS 111 trial is a multicenter, noncomparative pilot trial of early therapeutic drug monitoring in HIV-positive patients naïve for PI-containing HAART (16). Patients received a combination of two NRTIs plus one PI as antiretroviral therapy.…”
mentioning
confidence: 99%
“…This could initially be applied to all antiviral drugs, with a view to focus subsequently on more -targetable‖ drugs. This was already done by Duval et al [124], who showed that, among…”
Section: Implementing the Tdm In Clinical Settingsmentioning
confidence: 66%